Comparative analysis of goat and bovine milk proteins in the improvement of sarcopenia based on host-microbial interactions - Ruoyu Wang; Yuxin Ma; Meng Sun; Lutong Li; Zhaofeng Zhang (Food Science and Human Wellness)
IntroductionDiet intervention, especially supplementation with high-quality protein, is considered to be a critical strategy in sarcopenia. However, different sources and types of protein have different health impacts.ObjectivesThe aim of this study is to explore the differences in the ameliorative effects and mechanisms of different sources and types of proteins on sarcopenia, providing an optimal path for the prevention and treatment of sarcopenia.MethodsA sarcopenia model was established by intraperitoneal injection of dexamethasone (5 mg/kg). Sixty male C57BL/6 mice (8 months old) were randomly divided into the normal control, sarcopenia, goat whey protein, goat milk casein, bovine whey protein, and bovine milk casein groups. Animals were treated for 8 consecutive weeks. Organism-level and molecular phenotypes, 16S rRNA gene sequencing, and untargeted metabolomics profiling based on GC-TOF/MS were employed to investigate the correlation between host metabolism, microbial metabolism, autophagy and inflammation and their influence on sarcopenia in C57BL/6 male mice.ResultsAll 4 proteins increased muscle mass, and goat whey protein improved muscle strength in sarcopenic mice. Goat and bovine milk proteins promoted muscle regeneration by increasing MyoD1 and MyoG expression, and the former had a more distinct effect in inducing autophagy and decreasing inflammation than the latter. In addition, goat whey protein and casein could modulate host-microbial arginine co-metabolism. Notably, goat milk proteins responded well to sarcopenia comorbidities, including sarcopenic obesity, osteosarcopenia, and osteoarthritis.ConclusionThe study confirmed that goat milk proteins were more effective than bovine milk proteins for the control of sarcopenia. Moreover, we found that whey protein and casein could modulate host-microbial arginine co-metabolism, which shows their potential as precision nutritional supplements for the management of sarcopenia. Our study provides theoretical support for the prevention and control of sarcopenia.